(untitled) (Analysis in Theory and Applications, 2013)
The aim of this work is to generalize Szász-Mirakian operator in the sense of Stancu-Durrmeyer operators. We obtain approximation properties of these operators. Here we study asymptotic as well as rate of convergence results in simultaneous approximation for these modified operators.